The isolation of the antibody moieties of immune complexes from serum by the pepsin digestion of conglutinin-anti-conglutinin complexes. - Lachmann, P J (1981)
A technique is described which allows the antibodies of circulating immune complexes to be isolated as their F(ab')2 fragments. The method is based on the precipitation of the complexes by the sequential addition of conglutinin and anti-conglutinin, and the subsequent digestion of these precipitates by pepsin. Using this technique it has been possible to show antibodies to Epstein-Barr (EB) virus antigens in the immune complexes of patients with Burkitt's lymphoma and to microbial antigens in two patients with nephritis. By substituting DNAase for pepsin it has also been possible to show antibodies to DNA-containing nuclear antigens in the serum of patients with systemic lupus erythematosus.